Effect of combined fish oil & Curcumin on murine skeletal muscle morphology and stress response proteins during mechanical unloading - Lawler, John M.; Garcia-Villatoro, Erika L.; Guzzoni, Vinicius; Hord, Jeff M.; Botchlett, Rachel; Holly, Dylan; Lawler, Matthew S.; Janini Gomes, Mariana [UNESP]; Ryan, Pat; Rodriguez, Dinah; Kuczmarski, J. Matthew; Fluckey, James D.; et al. (Elsevier, 2019)
Skeletal muscle is a highly adaptable tissue capable of remodeling when dynamic stress is altered, including changes in mechanical loading and stretch. When muscle is subjected to an unloaded state (e.g., bedrest, immobilization, spaceflight) the resulting loss of muscle cross sectional area (CSA) impairs force production. In addition, muscle fiber-type shifts from slow to fast-twitch fibers. Unloading also results in a downregulation of heat shock proteins (e.g., HSP70) and anabolic signaling, which further exacerbate these morphological changes. Our lab recently showed reactive oxygen species (ROS) are causal in unloading-induced alterations in Akt and FoxO3a phosphorylation, muscle fiber atrophy, and fiber-type shift. Nutritional supplements such as fish oil and curcumin enhance anabolic signaling, glutathione levels, and heat shock proteins. We hypothesized that fish oil, rich in omega-3-fatty acids, combined with the polyphenol curcumin would enhance stress protective proteins and anabolic signaling in the rat soleus muscle, concomitant with synergistic protection of morphology. C57BL/6 mice were assigned to 3 groups (n = 6/group): ambulatory controls (CON), hindlimb unloading (HU), and hindlimb unloading with 5% fish oil, 1% curcumin in diet (FOC). FOC treatments began 10 days prior to HU and tissues were harvested following 7 days of HU. FOC mitigated the unloading induced decrease in CSA. FOC also enhanced abundance of HSP70 and anabolic signaling (Akt phosphorylation, p70S6K phosphorylation), while reducing Nox2, a source of oxidative stress. Therefore, we concluded that the combination of fish oil and curcumin prevents skeletal muscle atrophy due to a boost of heat shock proteins and anabolic signaling in an unloaded state.
Keywords: Anabolic; Atrophy; HSP70; Nox2; Nutraceutical; Skeletal Muscle; Spaceflight